Dimensions of Death-Related Attitudes in a French-Speaking Sample - Wittkowski, Joachim; Paré, Pierre-Marc (Omega-Journal of Death and Dying, 2021)
This study examines the structure of death-related attitudes among French-speaking people. Participants from Canada, Belgium, France, and from Switzerland whose mother tongue was French in an online survey responded to the French adaptation of the item pool of the Multidimensional Orientation Toward Dying and Death Inventory (MODDI; N = 373). Exploratory factor analyses with orthogonal and oblique rotation yielded a 5-factor Fear domain and a 3-factor Acceptance domain, thereby reproducing the a-priori conceptualization. These results are discussed with respect to the issue of universal dimensions of death-related attitudes across cultures.
CRIS-Team Scopus Importer:2021-09-17
Keywords: acceptance of dying and death; death-related attitudes; fear of dying and death

Introduction of the French version of the Multidimensional Orientation Toward Dying and Death Inventory (MODDI-F/fre) - Wittkowski, Joachim; Paré, Pierre-Marc (Death Studies, 2022)
Research on death-related attitudes needs complex assessment instruments for multicultural contexts. The French version of the Multidimensional Orientation Toward Dying and Death Inventory was factor analytically constructed with data from Europe and Canada (N = 370). The 24-item instrument with five and three scales in the fear and acceptance domain, respectively, shows favorable psychometric properties. The influence of social desirability is negligible. Women tended to express stronger fears and weaker acceptance of dying and death. Gender differences emerged concerning Fear of One’s Own Dying and Fear of Corpses, with women scoring higher than men on both dimensions. The importance of assessing attitudes toward dying and death transdiagnostically is outlined.
CRIS-Team Scopus Importer:2022-08-26